The importance of a hospital-dedicated sepsis response team. Issue 12 (1st December 2020) - Bloos, Frank
ABSTRACT: Introduction: As sepsis is a life-threatening disease, appropriate measures should be started as soon as possible after diagnosis. Duration until first therapy affects survival. However, guideline adherence of primary sepsis care is often low. Dedicated sepsis response teams (SRT) may improve primary sepsis care. Areas covered: PubMed was searched for studies investigating the effect of an implementation of SRTs. This review discusses the results of five studies presenting results before and after implementation of SRTs. The importance of choosing the alert and the right team composition of the SRT is also discussed. Expert opinion: Implementing SRTs is associated with a better compliance with guidelines regarding primary sepsis care and with a reduction in hospital mortality. However, scientific evidence of the studies is limited due to chosen study design. SRTs can be a strong method to improve primary sepsis care in specific hospital settings if the pros and cons against the other measures of quality improvement are considered and the technical details such as alerts and team members are customized to the individual hospital setting.